Pelaksanaan Pengawasan Kepala Sekolah dalam Meningkatkan Kedisiplinan Guru di UPTD SDN 089 Panyabungan - afridah afridah (Lembaga Intelektual Muda (LIM) Maluku, 2023)
Education is a place for humans to acquire knowledge in developing and changing mindsets in a better direction that is obtained in formal or non-formal education and with the aim of humanizing humans. The purpose of this study is to describe the implementation of the principal’s supervision in improving teacher discipline at UPTD SDN 089 Panyabungan. The location and place of this research is UPTD SDN 089 Panyabungan, which is located on Jl. Syekh Abdul Fattah Al-Mandily, Village of Kota Siantar, Panyabungan District, Mandailing Natal Regenci, Nort Sumatera Province. This study uses a qualitative apporoach with the techniques used in data collection, namely observation, interviews dan documentation. The results of the study are that teacher discipline is a person’s behavior as an educator and mentor which is carried out in accordance with applicable rules and norms. The principal has an important role in improving teacher discipline and what the principal does is by carrying out his function as a supervisor. As for the implementation of supervising the school principal in improving teacher discipline at the UPTD SDN 089 Panyabungan namely, planning, carrying out supervision, evaluating the results of supervision and making improvements.